2020
DOI: 10.3389/fnut.2020.00058
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Consumption of Bovine Dairy Milk Attenuates Dietary Saturated Fatty Acid-Induced Blood-Brain Barrier Dysfunction

Abstract: Ingestion of Western-diets enriched in long chain saturated fatty acids (LCSFA) are associated with increased risk of blood-brain barrier (BBB) dysfunction and neurovascular inflammation. Potential mechanisms include vascular insult as a consequence of metabolic aberrations, or changes in capillary permeability resulting in brain parenchymal extravasation of pro-inflammatory molecules. Bovine dairy milk (BDM) is potentially a significant source of dietary LCSFA, however, BDM contains an array of bioactive mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…HFD, rich in long-chain saturated fatty acids, permeates the hypothalamus across the BBB and directly activates microglia, which secrete proinflammatory molecules that inhibit GnRH neuron regeneration by acting on its receptors and reducing GnRH secretion by down-regulating kisspeptin signaling [28]. Previous evidences have shown that HFD-induced ovulation disorder is independent of the progression of obesity [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…HFD, rich in long-chain saturated fatty acids, permeates the hypothalamus across the BBB and directly activates microglia, which secrete proinflammatory molecules that inhibit GnRH neuron regeneration by acting on its receptors and reducing GnRH secretion by down-regulating kisspeptin signaling [28]. Previous evidences have shown that HFD-induced ovulation disorder is independent of the progression of obesity [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…HFDs enriched with long chain saturated fatty acids (LCSFAs) are known to directly impact the CNS (D'Alonzo et al., 2020 ; Milanski et al., 2009 ; Valdearcos et al., 2014 ). Excessive intake of dietary LCSFAs increases brain–blood barrier (BBB) permeability and induces BBB dysfunction (D'Alonzo et al., 2020 ). With an anatomical proximity to the BBB, the hypothalamus is the front‐line brain region that would be initially affected by any detrimental factors that are leaking through a dysfunctional BBB (Thaler et al., 2012 ).…”
Section: Hfd‐induced Hypothalamic Inflammation Is Involved In Hpo Axi...mentioning
confidence: 99%
“…3) High-fat diet induces pathological hypothalamic microglia activation. HFDs enriched with long chain saturated fatty acids (LCSFAs) are known to directly impact the CNS (D' Alonzo et al, 2020;Milanski et al, 2009;Valdearcos et al, 2014). Excessive intake of dietary LCSFAs increases brain-blood barrier (BBB) permeability and induces BBB dysfunction (D' Alonzo et al, 2020).…”
Section: Hfd-induced Hypothalamic Inflammation Is Involved In Hpo Axi...mentioning
confidence: 99%